Teologi Misi sebagai Teologi Amanat Agung - Fransiskus Irwan Widjaja; Daniel Ginting; Sabar Manahan Hutagalung (Badan Musyawarah Perguruan Tinggi Keagamaan Kristen Indonesia, 2019)
From the beginning of human creation, God's call never changes. Since the first man fell into sin, God has continued to take the initiative to look for the lost, from the old covenant to the new covenant and even himself sent, but to this day, the world is still not evangelized. Jesus himself was present for three and a half years, and sent twelve disciples, even the calling and commission of the Great Commission was continued by the church and believers, but from the facts and facts, the world was still not entirely accessible. After two thousand years, the call and commission of the Great still cannot be fulfilled. This article is a reflective study using a hermeneutical approach to biblical texts that speak of the great commission of Jesus Christ. Mission theology is the theology of the Great Commission needs to be developed to complete. AbstrakDari awal penciptaan manusia, panggilan Allah tidak pernah berubah. Sejak manusia pertama jatuh dalam dosa, Allah terus berinisiatif mencari yang terhilang, dari perjanjian lama sampai perjanjian baru bahkan diriNya sendiri di utus, tetapi sampai hari ini, dunia masih tetap belum terinjili. Yesus sendiri hadir selama tiga setengah tahun, dan mengutus dua belas murid, bahkan panggilan dan tugas Amanat Agung dilanjutkan oleh gereja dan orang percaya, tetapi dari fakta dan kenyataan, dunia masih belum seluruhnya terjangkau. Setelah dua ribu tahun, panggilan dan amanat Agung tetap belum bisa digenapi. Artikel ini merupakan kajian reflektif dengan menggunakan pendekatan hermeneutis atas teks-teks Alkitab yang berbicara tentang amanat agung Yesus Kristus. Teologi misi merupakan teologi Amanat Agung perlu dikembangkan untuk menuntaskan.